2021
DOI: 10.1007/s13132-021-00838-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Income Inequality Influenced by Financial Knowledge? A Macroeconomic and Longitudinal Analysis

Abstract: Our objective is to analyze whether financial knowledge influences income inequality. For this purpose, we resort to a new index of financial knowledge that differs from the existing ones in that it is both longitudinal and macroeconomic. We use this index as one of the explanatory variables of the Net Gini Index in our panel data estimations. Based on a sample of 63 countries over the period 2008–2014, our results allow us to conclude that financial knowledge is related to income inequality and that, moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Pong, (2022) identified that financial attitudes are the outcome of the particular behavior of a decision-maker, and the attitude can be through their economic and non-economic beliefs. Polisetty et al, (2021) and Oliver-Márquez et al, (2022) concluded that education could improve personal financial attitude. Financial attitudes, along with financial behavior, can also affect financial well-being.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pong, (2022) identified that financial attitudes are the outcome of the particular behavior of a decision-maker, and the attitude can be through their economic and non-economic beliefs. Polisetty et al, (2021) and Oliver-Márquez et al, (2022) concluded that education could improve personal financial attitude. Financial attitudes, along with financial behavior, can also affect financial well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the external locus of control tends to assume that life is determined by environmental forces (Oliver-Márquez et al, 2022). According to Mutamimah et al, (2021) in his research, locus of control positively affects financial behavior.…”
Section: H2: Financial Attitude Has a Positive Influence On Financial...mentioning
confidence: 99%
“…The GINI coefficient is measured as a scale from 0 to 1 (rescaled here to percentages), with zero indicating complete inequality and 100 indicating complete equality. Including the GINI coefficient is inspired by other work on the correlation between inequality and economic (Lo Prete, 2018) or financial literacy (Lusardi et al, 2017; Oliver‐Márquez et al, 2022). Other recent literature has shown that the GINI coefficient is negatively correlated with financial literacy, arguing that increased social comparison due to financial inequality can negatively affect financial literacy (Peng et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…There is a large and growing body of literature on the effect of financial knowledge on financial decisions, for example, savings, investing, borrowing (Bönte & Filipiak, 2012;Lusardi & Mitchell, 2007Van Rooij et al, 2011), income inequality (Oliver-Márquez et al, 2021), and access to FinTech services (Hasan et al, 2022), but very little is known about the effect of financial knowledge on entrepreneurial intentions. The associations between financial knowledge, the three motivational factors, and entrepreneurial intentions are unclear in the literature (Ćumurović & Hyll, 2019;Dohse & Walter, 2012;Oseifuah, 2010).…”
Section: Financial Knowledgementioning
confidence: 99%